Development of Disaster Mitigation and Adaptation Learning Tools With Sets Vision (Science, Environment, Technology, Society) Geography Subject in SMA Negeri Palu - Nisa', Zumrotin; Saputra, Iwan Alim; Rahmawati, Rahmawati; Putra, Exsa (Universitas Lambung Mangkurat, 2023)
This research aims to develop teaching resources for disaster mitigation and adaptation that are integrated into geography subject with a focus on Science, Environment, Technology, and Society (SETS). Up until stage three define, design, and develop research and development processes are conducted using 4D models. Small-group product trials were conducted as an experimental class. The trial findings suggest that the designed learning gadget is valid, practical, and effective. Expert-validated items have a respectable qualification of 80% for their continued existence. Teachers rated the learning device's practicality at 89.93%, whereas students gave it a rating of 77.97% for SETS learning and 75.50% for courses on disaster mitigation and adaptation. With a score of 0.40, the effectiveness test findings were deemed effective in the medium category. Therefore, the prepared syllabus, lesson plans, modules, and assessments that are the result of learning tools for geography subjects in class XI social studies for Disaster Mitigation material with a SETS vision are appropriate for use as learning tools.